PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR MATA PELAJARAN MEKANIKA TEKNIK DAN ELEMEN MESIN KELAS X TP-3 DI SMK MUHAMMADIYAH 3 YOGYAKARTA TAHUN PELAJARAN 2015 / 2016 - Ahmad Nurdiansyah; setuju setuju (Jurnal Taman Vokasi, 2016)
This research aims are: (1) to improve the students’ learning activities (2) to improve the students’ learning result on the lesson of engineering mechanics and machine element by the tenth grade of TP-3 SMK Muhammadiyah 3 Yogyakarta in academic year 2015/2016.The type of this research is action research by applying the Cooperative Learning Model; Type of Jigsaw that had been done in TP-3 SMK Muhammadiyah 3 Yogyakarta in Academic Year 2015/2016. The subject of this research were the students that consists of 25 students. This research used observation and test for the data collecting technique. The data analysis technique used descriptive quantitative.The result of this research shows that (1) The application of Cooperative Learning Model; Type of Jigsaw on Engineering Mechanics can improve the activities of students learning of the tenth grade of  TP-3 SMK Muhammadiyah 3 Yogyakarta. (2) The application of Cooperative Learning Model; Type of Jigsaw can improve the result of students learning of the tenth grade of  TP-3 SMK Muhammadiyah 3 Yogyakarta. It can be seen on the development of  the students learning activities that shows the average is 57.99% in cycle I, it increased in cycle II become 75.14%, then it increases again become 79.71% in cycle III. While the score of the learning result shows that the average of the score in cycle I is 63.2. In cycle II the students learning result increase become 75. Then, in cycle III, the students learning result increase become 81.4. Thus, can be concluded that The Application of Cooperative Learning Model; Type of Jigsaw can Improve the Activities and the Learning Result on the Lesson of Engineering Mechanics and Machine Element by the Tenth Grade of TP-3 SMK Muhammadiyah 3 Yogyakarta